Cerebellar and Spinal Direct Current Stimulation in Children: Computational Modeling of the Induced Electric Field - Fiocchi, Serena; Ravazzani, Paolo; Priori, Alberto; Parazzini, Marta (Frontiers in Human Neuroscience, 2016)
Recent studies have shown that the specific application of transcranial direct current stimulation (tDCS) over the cerebellum can modulate cerebellar activity. In parallel, transcutaneous spinal DC stimulation was found to be able to modulate conduction along the spinal cord and spinal cord functions. Of particular interest is the possible use of these techniques in paediatric age, since many pathologies and injuries, which affect the cerebellar cortex as well as spinal cord circuits, are diffuse in adults as well as in children. Up to now, experimental studies of cerebellar and spinal DC stimulation on children are completely missing and therefore there is a lack of information about the safety of this technique as well as the appropriate dose to be used during the treatment. Therefore, the knowledge of electric quantities induced into the cerebellum and over the spinal cord during cerebellar tDCS and transcutaneous spinal DCS, respectively, is required. This work wants to address this issue by estimating, through computational techniques, the electric field distributions induced in the target tissues during the two stimulation techniques applied to different models of children of various ages and gender. In detail, we used four voxel child models, aged between 5- and 8-years. Results revealed that, despite inter-individual differences, the cerebellum is the structure mainly involved by cerebellar tDCS, whereas the electric field generated by transcutaneous spinal direct current stimulation can reach the spinal cord also in children. Moreover, it was found that there is a considerable spread toward the anterior area of the cerebellum and the brainstem region for cerebellar tDCS and in the spinal nerve for direct current spinal stimulation. Our study therefore predicts that the electric field spreads in complex patterns that strongly depend on individual anatomy, thus giving further insight into safety issues and informing data for paediatric investigations of these stimulation techniques.